2003
DOI: 10.2460/ajvr.2003.64.672
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium disodium EDTA and meso-2,3-dimercaptosuccinic acid on tissue concentrations of lead for use in treatment of calves with experimentally induced lead toxicosis

Abstract: DMSA is much more effective than EDTA in removing lead from renal and hepatic tissues in calves. Use of DMSA in calves with lead intoxication appears to be a viable treatment option. Combining DMSA and EDTA as a treatment modality in calves did not offer any advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…It has also been shown that combination of thiamine with CaEDTA is more effective than the respective individual treatments alone [1,29].The results of the present study show that the lowering effect of allicin on blood lead level and lead content of different tissues of sheep is superior to previous reports about thiamine [26,28,30]. Allicin is highly effective in removing lead from bone while, CaEDTA and MesoDMSA, the conventional lead chelators, were unable to decrease bone lead content when used in calves [9]. On the other hand, allicin has several advantages over those chelators; it is administered orally and effective in sheep, a ruminant with special gastrointestinal tract which usually restricts oral administration of drugs.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…It has also been shown that combination of thiamine with CaEDTA is more effective than the respective individual treatments alone [1,29].The results of the present study show that the lowering effect of allicin on blood lead level and lead content of different tissues of sheep is superior to previous reports about thiamine [26,28,30]. Allicin is highly effective in removing lead from bone while, CaEDTA and MesoDMSA, the conventional lead chelators, were unable to decrease bone lead content when used in calves [9]. On the other hand, allicin has several advantages over those chelators; it is administered orally and effective in sheep, a ruminant with special gastrointestinal tract which usually restricts oral administration of drugs.…”
Section: Discussioncontrasting
confidence: 69%
“…Although these compounds are widely used as lead chelators, none are suitable in reducing lead burden in chronic lead exposures [7]. Moreover, the conventional chelators are compromised with many side effects and drawbacks and there is no safe and effective treatment available for lead poisoning [8][9][10][11]. On the other hand, none of the chelating agents are approved for use in food animals [9].…”
Section: Introductionmentioning
confidence: 99%
“…Heparinized whole blood samples (0.5 ml/bird) were frozen at À808C and shipped on dry ice, along with the Pb pellets, also for Pb analysis. The method described by Meldrum and Ko [13] was used. The spiked source was acquired from Wisconsin State Laboratory of Hygiene and tested with each run.…”
Section: Pellet and Blood Pb Analysismentioning
confidence: 99%
“…The measurement of the seminiferous tubule and volume estimation of the total testis volume will be valuable especially in the toxicological research and the determination of the environmental pollution. The environmental polluters such as pesticides and heavy metals causes disorders on the reproductive activity and the impairment on the germ cell in the testis of the mammals (Bonde, 2010;Fejes et al, 1991;Meldrum & Ko, 2003;Ince et al;Michael et al, 2007;Bailey et al, 2004). In conclusion, in this research we estimated the testicular weight, length, width, volume and the diameters of the seminiferous tubules and could not detected statistically importance in groups or between sexes (p>0.05).…”
Section: Discussionmentioning
confidence: 77%